BANK FINANCIAL SOUNDNESS IN INDONESIA: EVIDENCE FROM THE COVID-19 PANDEMIC AND THE POST-PANDEMIC PERIOD - Embuningtiyas, Sandra Sukma; Puspasari, Oktaviani Rita; Prasetya, Fandi (Program Studi Akuntansi, Universitas Kuningan, 2024)
This study aims to analyze the bank financial of soundness of conventional banking in Indonesia during the COVID-19 pandemic and post-pandemic. Bank financial of soundness assessment is carried out using the Risk-Based Bank Rating approach through the RGEC method (Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital). This research is descriptive quantitative with secondary data obtained from the Annual Report and GCG Report of conventional banks listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The results showed that overall, the health level of the banks studied was classified as “Healthy” both during the pandemic and post-pandemic, with the best performance shown in the aspects of capital and governance (GCG). Meanwhile, the profitability aspect shows a fairly good performance, although it is not evenly distributed across all indicators measured. In the risk profile aspect, the majority of banks show a very healthy Non-Performing Loan (NPL) ratio but not the LDR ratio. The results also show that there is an increasing trend from year to year for the number of banks in the very healthy category, while the number of banks in the less healthy category tends to decrease, especially from the beginning of the pandemic to post-pandemic. The implication of this finding is that the resilience of Indonesian banks is quite good in facing the crisis caused by the Covid 19 pandemic. However, strengthening liquidity management strategies is needed to strengthen stability in the long run. These results can serve as input for regulators in formulating financial risk mitigation policies as well as for bank management in improving governance practices and operational efficiency.